Analisis Strategi Perencanaan dan Pengembangan Sumber Daya Manusia pada Sentral Yamaha Padang sebagai Upaya Meningkatkan Kinerja Karyawan - Fikri, Hasanul; Wahyu, Fauzi; Kurniawan, Fikri; Asodepa, Alresna Ramadhani; Putra, Ramdani Bayu; Fitri, Hasmaynelis (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
Human resources (HR) are an important asset for the success of a company, especially in a competitive automotive sector such as Sentral Yamaha Padang. Facing the challenges of market competition and changes in consumer behavior, companies are required to develop comprehensive and innovative HR strategies. Sentral Yamaha Padang faces significant problems in the form of budget constraints, inadequate employee mapping, work culture and others. This condition indicates a gap in the HR management system that requires strategic and sustainable solutions. This activity aims to analyze effective HR strategy planning and development in improving employee performance at Sentral Yamaha Padang, as well as reviewing the implementation of a technology-based workforce optimization system to create a productive and competitive work environment. The activity was carried out using an interview and observation approach involving selected managers and employees. The implementation of HR planning and development strategies in the form of ongoing training programs, performance-based reward systems, clear communication, motivating employees and maintaining work-life balance.